Story of England [videorecording (DVD)] - Wood, Michael, 1948- (BBC, 2012)
Michael Wood tells the story of one place, the village of Kibworth, Leicestershire, throughout the whole of English history. Located in the very heart of England, Kibworth has lived through the Black Death, the Civil War and the Industrial Revolution, and was even bombed in World War II. With the help of the local people and using archaeology, landscape, language and DNA, Michael Wood uncovers the lost history of this village from the Roman era to the present day.